Penerapan Pilar Green Economy dalam Pengembangan Desa Wisata Ngringinrejo Kalitidu Bojonegoro - Dwik Pujiati; Aji Damanuri (Institut Agama Islam Negeri Ponorogo, 2022)
This research was motivated by the anxiety of the people of Ngringinrejo Village, located on the banks of the Bengawan Solo river, because it often experiences crop failure during the rainy season. Natural disasters are one of the impacts of irresponsible economic activities, for example, illegal sand mining, logging in mixed forests, dumping industrial waste into rivers, etc. This study aims to describe and analyze the process of implementing the three pillars of the green economy, namely the economic, social, and ecosystem (environment) pillars in Ngringinrejo Starfruit Agrotourism. This research approach uses qualitative research (field research). Data collection techniques using observation, interviews, and documentation. The results of this study indicate that the agro-tourism of the Ngringinrejo star fruit garden has an impact on improving the economy, society, and ecosystem. Based on the economic pillar, there is an increase in the income of the people who are members of this primary tourism group. The growth occurs because every day there will be visitors who come and always buy star fruit for souvenirs. From a social point of view, this agro-tourism has involved many stakeholders who influence the number of workers needed. Even residents who do not own land can rent it to sell star fruit or other products. Meanwhile, in terms of ecosystems, star fruit trees have a lot of water absorption, have an average age of about 20 years, and bear fruit throughout the year.